Exploring the Impact of Public Debt on Insecurity In Nigeria - Manir Umar; Zubairu Muhammad Suleiman (CV. Syntax Corporation Indonesia, 2024)
This study investigated the impact of public debt on insecurity in Nigeria. In the analysis, the study also sought to estimate how poverty, unemployment and level of education can affect insecurity in Nigeria. The study however, used annual time-series data covering the period from 1982-2023 using Autoregressive Distributed Lag Model (ARDL) as technique of data analysis. From the econometrics results the study revealed that unemployment, poverty have a significant positive influence on insecurity in Nigeria. Further, public debt and level of education also have a significant positive effect on insecurity in Nigeria over the sampled period. Based on the results, the study recommended that government should tackle corruption in the defense sector this is because the correlation between corruption and insecurity is positive. The need to provide and improve education and job opportunities to teaming graduates should also be prioritized. With access to quality education and job opportunities youth and fresh graduates will be able to lead production lives and make positive contribution.